Occupation-related Information Seeking Behaviour Models: A Comparative Study - Ramasamy A.; Ali N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Information retrieval; Information use; Behaviour models; Comparative studies; Information behaviours; Information seeking behaviours; Qualitative research methods; Behavioral research